2019
DOI: 10.3389/fgene.2019.00184
|View full text |Cite|
|
Sign up to set email alerts
|

Associations Between Behavioral Effects of Bisphenol A and DNA Methylation in Zebrafish Embryos

Abstract: Endocrine-disrupting contaminants have been associated with aberrant changes in epigenetic pathways in animals. In this study, zebrafish embryos were exposed bisphenol A (BPA) to search for associations between behavior and epigenetic mechanisms in fish. For concentration-dependent responses, embryos were exposed to a range of BPA concentrations (0.1 nM to 30 μM). Embryos were analyzed for locomotor activity at 3-, 4-, and 5-days post fertilization (dpf) in response to changing light conditions. Based on conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 87 publications
5
31
0
1
Order By: Relevance
“…Finally, the study that reported the largest number of genes also found as DMC-related genes in sea bass ( n =15) was by Gavery et al [45]; These authors were interested in the liver of hatchery vs wild rainbow trout during a so-called ‘temporal analysis’ (see Additional File 5). Another study on zebrafish reported 11 genes in common with the present study, but was not organ specific (see Additional File 5) [53].…”
Section: Resultssupporting
confidence: 59%
“…Finally, the study that reported the largest number of genes also found as DMC-related genes in sea bass ( n =15) was by Gavery et al [45]; These authors were interested in the liver of hatchery vs wild rainbow trout during a so-called ‘temporal analysis’ (see Additional File 5). Another study on zebrafish reported 11 genes in common with the present study, but was not organ specific (see Additional File 5) [53].…”
Section: Resultssupporting
confidence: 59%
“…Finally, the study that reported the largest number of genes also found as DMC-related genes in sea bass (n =15) was by Gavery et al [45]; These authors were interested in the liver of hatchery vs wild rainbow trout during a so-called 'temporal analysis' (see Additional File 5). Another study on zebra sh reported 11 genes in common with the present study, but was not organ speci c (see Additional File 5) [53].…”
Section: Literature Surveyssupporting
confidence: 61%
“…In fish, genome-wide DNA methylation studies have been conducted to uncover the epigenetic effects on muscular polyunsaturated fatty acid metabolism of the common carp ( Cyprinus carpio ) (Zhang et al, 2019a), skin color variations in crucian carp [ Carassius carassius L. (Zhang et al, 2017b) and C. carpio (Li et al, 2015)], behavioral effects of zebrafish ( Danio rerio ) (Olsvik et al, 2019), the evolution of heteromorphic sex chromosomes of three-spine stickleback ( Gasterosteus aculeatus ) (Metzger and Schulte, 2018), sexual dimorphism of hybrid tilapia ( Oreochromis spp.) (Wan et al, 2016), sex determination of C. semilaevis (Shao et al, 2014), growth of large yellow croaker ( Larimichthys crocea ) (Zhang et al, 2019b), thermal acclimation of G. aculeatus (Metzger and Schulte, 2017), and so on.…”
Section: Introductionmentioning
confidence: 99%